Pop of the bumpy mummy - Cummings, Troy (Cummings, Troy. Notebook of doom, 2015)
Alexander's class is going on a sleepover at the Stermont Museum, but something is stealing bright, shiny objects from all over town, including the museum's treasured Ruby Scorpion, and on the night of the visit the young monster hunters finally confront the town's newest monster--a warrior covered entirely by bubble-wrap.